2012
DOI: 10.1002/14651858.cd009157.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium versus long-acting beta-agonists for stable chronic obstructive pulmonary disease

Abstract: This review is published as a Cochrane Review in the Cochrane Database of Systematic Reviews 2012, Issue 9. Cochrane Reviews are regularly updated as new evidence emerges and in response to comments and criticisms, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 92 publications
5
48
0
3
Order By: Relevance
“…In a systematic review of seven randomised trials that directly compared a LAMA (i.e. tiotropium) with LABAs, meta-analyses found that the LAMA had a greater effect on reducing COPD exacerbations, exacerbation-related hospitalisations, and adverse effects, but there were no differences in mortality, all-cause hospitalisations, symptoms, or lung function [131].…”
Section: Standard Pharmacological Therapiesmentioning
confidence: 99%
“…In a systematic review of seven randomised trials that directly compared a LAMA (i.e. tiotropium) with LABAs, meta-analyses found that the LAMA had a greater effect on reducing COPD exacerbations, exacerbation-related hospitalisations, and adverse effects, but there were no differences in mortality, all-cause hospitalisations, symptoms, or lung function [131].…”
Section: Standard Pharmacological Therapiesmentioning
confidence: 99%
“…Moreover, according to the results of many studies, tiotropium shows an equivalent effect with long-acting β 2 agonists in many parameters, such as the rates of hospitalization and pulmonary functions and the improvement of symptoms in COPD treatment (16).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of seven randomised trials that directly compared a LAMA (i.e. tiotropium) with LABAs, meta-analyses found that the LAMA had a greater effect on reducing COPD exacerbations, exacerbation-related hospitalisations and adverse effects, but there were no differences in mortality, all-cause hospitalisations, symptoms or lung function [89]. The meta-analyses were limited by heterogeneity, suggesting that the differences between the LAMA and LABAs may have been due to the specific LABA (i.e.…”
Section: Standard Pharmacological Therapiesmentioning
confidence: 99%